The Therapeutic Effectiveness of Neoadjuvant Trastuzumab Plus Chemotherapy for HER2-Positive Breast Cancer Can Be Predicted by Tumor-Infiltrating Lymphocytes and PD-L1 Expression - Shang, Mao; Chi, Yajing; Zhang, Jianbo; Chang, Jin; Yang, Hui; Yin, Sha; Tan, Qiaorui; Man, Xiaochu; Li, Huihui (Frontiers in Oncology, 2022)
Introduction: Currently, the standard neoadjuvant therapy for stage II-III HER2-positive breast cancer is trastuzumab plus chemotherapy, but approximately 25% of patients still progress after treatment. An urgent need for a biomarker that can predict the effect of this treatment to identify the people who will benefit. Methods:HER2-positive breast cancer cases received NAT (n=155) were retrospectively collected from July 2013 to November 2018. Histopathologic analysis of TILs was performed on hematoxylin and eosin (H&E)–stained sections from the pre- and post-NAT specimens. TILs score as a categorical variable can be divided into high (≥30%) and low (<30%) categories. The expression of PD-L1 was detected by immunohistochemistry and the percentage of positive membranous staining (at least 1%) in tumor cells (PD-L1+TC) and TILs (PD-L1+TILs) was scored respectively. Results: In our study, 87 patients received neoadjuvant chemotherapy alone, and 68 patients received neoadjuvant trastuzumab plus chemotherapy. Multivariate logistic regression analysis confirmed that lymph node metastasis, high TILs and PD-L1+TILs in pre-neoadjuvant therapy specimens were independent predictors of pCR in neoadjuvant therapy(P<0.05, for all).Among all patients, TILs increased in breast cancer tissues post-neoadjuvant therapy (P<0.001). Consistent results were found in subgroup analysis of trastuzumab plus chemotherapy group and chemotherapy alone group (P<0.05,for both). In 116 non-pCR patients, PD-L1+TC decreased in breast cancer tissues post-neoadjuvant therapy (P=0.0219). Consistent results were found in 43 non-pCR patients received neoadjuvant trastuzumab plus chemotherapy (P=0.0437). While in 73 non-pCR patients received neoadjuvant chemotherapy, there was no significant difference in PD-L1+TC expression in pre- and post-neoadjuvant therapy specimens (P=0.1465). On the other hand, in the general population, neoadjuvant trastuzumab plus chemotherapy group and neoadjuvant chemotherapy group, PD-L1+TILs all decreased after treatment (P<0.05,for both). Conclusion: Higher TILs count and PD-L1+TILs in pre-neoadjuvant therapy specimens and lymph node metastasis were independent predictors of pCR in patients with HER2-positive breast cancer treated with neoadjuvant therapy.TILs count, PD-L1 + TC and PD-L1 + TILs all changed before and after neoadjuvant trastuzumab plus chemotherapy for HER2-positive breast cancer, which may suggest that in HER2-positive breast cancer, neoadjuvant trastuzumab plus chemotherapy may stimulate the anti-tumor immune effect of the organism, thereby preventing tumor immune escape.